SOFT SKILLS AS A KEY COMPETENCY FOR THE FUTURE LEADERS OF THE HOSPITALITY INDUSTRY - Anusha Pai , Maitri Manjunath , C S Suhas Kowshik ,Nishu Ayedee , Namesh Malarout , Nithesh Naik (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
The essential skills that rapidly evolve in the hospitality industry demand a frequentreview and update in the academic curriculum in order to satisfy the increasing job prospects as well as the performance requirements for hospitality graduates. This research explores the essential key competencies and soft skills, the hospitality industry expects fromhotel managers, hotel management graduates and hotel management trainees. A cross-sectional survey conducted includingstudents of hotel management school and hospitality managers of 5-star hotels in India, showed that, 86% were soft competencies out of which,flexibility, integrity, interpersonal skills, positive attitude, professionalism, work environment, communication, responsibility, and teamwork are some of the key skillsthat play a major role.The results indicate that hospitality programs should focus on the development of soft skills in support of hard skills among the students.